2019
DOI: 10.1002/mus.26396
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation in early rehabilitation of Guillain‐Barré syndrome: A pilot study

Abstract: Introduction: In Guillain‐Barré syndrome (GBS), patients often develop muscle atrophy from denervation and immobilization. We, therefore, conducted a pilot study of neuromuscular electrical stimulation (NMES) to evaluate feasibility, safety, and effect on muscle wasting in the early phase of GBS. Methods: Seventeen patients were randomized to receive 20 min of muscle fiber stimulation followed by 40 min of NMES of the right or left quadriceps muscle with the untreated side as control. Cross‐sectional area (CSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
8
0
6
Order By: Relevance
“… 8 , 9 In this study, the subjects showed minimal change in the thickness of the VL muscle. The results of this report support previous findings 8 , 11 , 13 and suggest that the use of EMS to treat muscles with paralysis seems safe and feasible in the early phase of NMO.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 8 , 9 In this study, the subjects showed minimal change in the thickness of the VL muscle. The results of this report support previous findings 8 , 11 , 13 and suggest that the use of EMS to treat muscles with paralysis seems safe and feasible in the early phase of NMO.…”
Section: Discussionsupporting
confidence: 90%
“…A study on EMS intervention for Guillain-Barré syndrome, a demyelinating disease similar to NMO, has recently been reported. 11 Harbo et al 11 reported that EMS intervention tended to inhibit muscle mass loss more than no intervention ( p = 0.08) and seemed safe and feasible in the early phase of Guillain-Barré syndrome. EMS has been found effective for muscle atrophy caused by bed rest, 12 immobilization, 7 and nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, Fried et al proposed shrinking, weakness, exhaustion, slowness, and low activity as diagnostic criteria that are easily adaptable to clinical practice [ 1 ]. Symptoms are more likely to progress in an infectious or inpatient setting, and early hospital discharge and rehabilitation are effective [ 3 - 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies that investigated the effect of ES in GBS. A pilot study applied neuromuscular as well as direct muscle stimulation in the early stage of GBS [30] with the aim to avoid disuse and denervation atrophy of the quadriceps muscle during the neurological recovery [30] . In that study, the GBS disability score improved significantly but not muscle strength.…”
Section: Discussionmentioning
confidence: 99%